List Price Collusion - Willem H. Boshoff; Johannes Paha (Journal of Industry, Competition and Trade, 2021)
Firms sometimes collude by agreeing on increases in list prices. Yet, the efficacy of such list price collusion is subject to discussion as colluding firms might, in principle, deviate secretly from the elevated prices by granting their customers discounts. This article reviews cases of list price collusion in the USA and Europe, and it presents a theory of harm suggesting that a combination of anchoring, orientation on reference points, and loss aversion may render list price collusion effective in raising transaction prices—even if firms set transaction prices in a non-coordinated fashion.
Keywords: 690; List price; Collusion; Discount; Cartel; Antitrust; Anchoring; Reference prices